A project study on the expansion of Alma-tech a sub-contracting firm for garments in Quezon City - Matta, August Pearl S.; Cruz, Agerico V. (1990.)
The objective of the study was to find out whether it is feasible to expand the manufacturing capacity of a garment firm, such as Alma-Tech. Corollary to the objective, the study attempted to answer the following problems: 1) Is it feasible to expand the production capacity of a sub-contracting garment firm, such as Alma-Tech, and 2) Will the same garment firm profit from the expansion. Alma-Tech is located at Number 23 Matalino Street, in Diliman, Quezon City. A questionnaire was used for obtaining data through a series of personal interviews with the owner-manager of Alma-Tech, Ms. Evelyn Bernabe. The findings and conclusion in the financial analysis of the study showed that firm will profit from the expansion. This is an indication that the proposed project is feasible.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing factories -- Philippines -- Quezon City